Quantifying the long-term impact of zoological education: a study of learning in a zoo and an aquarium. Issue 7 (2nd July 2020) - Collins, Courtney; Corkery, Ilse; McKeown, Sean; McSweeney, Lynda; Flannery, Kevin; Kennedy, Declan; O'Riordan, Ruth
Abstract: There is increasing evidence that zoos and aquariums do, as intended, educate their visitors. However, even though most zoos offer a wide array of educational experiences, few studies have considered if the duration of an educational experience affects learning or whether learning lasts beyond the immediate visit. The current study used matched-pairs surveys to investigate children's knowledge, attitude and knowledge of positive behavior during both a five-day zoo camp and six months after an aquarium visit. The participants of the study included children aged 9–12 years some of whom had participated in a purposefully designed educational intervention. First, the impact of a five-day zoo camp experience on children's learning was investigated. Second, learning retention was investigated six months after a school tour at an aquarium. Results showed that during the camp learning was positively affected by participation in the educational intervention and by previous zoo experience. Girls were more likely than boys to have an increase in learning six months after an aquarium visit. The study demonstrates that learning persists, but that education can be enhanced with longer programs. Thus, zoos can play an increasingly important role in igniting pro-environmental behavior.